Cis‐prenyltransferase 3 and α/β‐hydrolase are new determinants of dolichol accumulation in Arabidopsis. (29th November 2021) - Gawarecka, Katarzyna; Siwinska, Joanna; Poznanski, Jaroslaw; Onysk, Agnieszka; Surowiecki, Przemyslaw; Sztompka, Karolina; Surmacz, Liliana; Ahn, Ji Hoon; Korte, Arthur; Swiezewska, Ewa; Ihnatowicz, Anna
Abstract: Dolichols (Dols), ubiquitous components of living organisms, are indispensable for cell survival. In plants, as well as other eukaryotes, Dols are crucial for post‐translational protein glycosylation, aberration of which leads to fatal metabolic disorders in humans and male sterility in plants. Until now, the mechanisms underlying Dol accumulation remain elusive. In this study, we have analysed the natural variation of the accumulation of Dols and six other isoprenoids among more than 120 Arabidopsis thaliana accessions. Subsequently, by combining QTL and GWAS approaches, we have identified several candidate genes involved in the accumulation of Dols, polyprenols, plastoquinone and phytosterols. The role of two genes implicated in the accumulation of major Dols in Arabidopsis—the AT2G17570 gene encoding a long searched for cis ‐prenyltransferase (CPT3) and the AT1G52460 gene encoding an α/β‐hydrolase—is experimentally confirmed. These data will help to generate Dol‐enriched plants which might serve as a remedy for Dol‐deficiency in humans. Summary Statement: The accumulation of Dolichols in Arabidopsis is affected by the cis‐prenyltransferase 3 (CPT3) and an α/β‐hydrolase (ABH). Using QTL and GWAS approaches we have identified these two and several other candidate genes involved in the accumulation of Dols, polyprenols, plastoquinone and phytosterols.